SMART monitoring and treatment of fracture healing: Piezoelectric transducers and stepper motor actuators - Antić, Vladimir D.; Protić, Danijela D.; Stanković, Miomir M.; Manić, Miodrag T. (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: SMART orthopedic systems use fixators with remote monitoring, processing, and communication capabilities to leverage healing progression data for personalized, real-time monitoring of a healing process. The fixators incorporate small and compact piezoelectric sensors that generate electrical signals upon the application of force to the piezoelectric diaphragm. This enables doctors to remotely guide fixation devices using indirectly and remotely controlled stepper motors known for their precision and accuracy. Reliability of stepper motors makes them a viable alternative for the mechanical tools traditionally used by doctors for fixator extension.Methods: This study focuses on the evaluation of sensor-based technology in orthopedic applications. The paper presents a theoretical framework for the application of SMART devices in the bone fracture healing process. It delves into the structure and functionality of piezoelectric transducers, offering a comprehensive insight into this technology and various engineering aspects of SMART systems.Results: The implementation of SMART systems has significantly enhanced doctor-patient communication. This improvement is facilitated through a dual-phase process involving gathering, processing, and transmitting the data wirelessly from the patient’s (sensor) interface to the doctor who uses specialized software for data analysis and wireless transmission to the stepper motor actuator. Subsequently, the data is forwarded to the decoder at the motor site, where a motor controller generates the control signal for the stepper motor driver.Conclusion: SMART implants can provide doctors with quantitative data that can be used in directing a rehabilitation plan. The sensor-based technology offers insights into the stress induced by the callus formation enabling bidirectional communication between the doctor and the patient. The stepper motor is a tool that aids in personalized treatment from the distance.
Keywords: SMART implant; piezoelectric sensor; fracture healing; stepper motor